Efecto de la fertilización con Nitrógeno y Calcio, en el incremento de biomasa del pasto saboya (Megathyrsus maximus Jacq.) irradiado a 52 Gy, en la zona de Babahoyo - Mendoza Carreño, Daniela Jazmín (2020)
This experimental work was carried out on the grounds of the Experimental Farm "San Pablo" of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7 ½ of the Babahoyo - Montalvo road. The genetic material used was the Savoy grass that is found planted in the facilities of the Faculty of Agricultural Sciences of the Technical University Babahoyo. Nitrogen and Calcium-based treatments were evaluated, such as Nitrogen + Calcium in doses of 150 kg / ha of N + 2.0 L CaO and 100 kg / ha of N + 1.0 L CaO; Nitrogen in a dose of 100 kg / ha of N; Calcium in 1.0 L CaO dose and an absolute control. The applications of the treatments were made 30, 60 and 90 days after the start of the trial, according to each of the established cuts. The experimental design was Completely Random Blocks with five treatments and four repetitions, using the Tukey test at 95% probability. Based on the results, it was determined that the fertilization with Nitrogen and Calcium caused favorable effects in the biomass increase of the saboya grass irradiated to 52 Gy, in the Babahoyo area; the application of nitrogen in doses of 100 kg / ha influenced so that there is a higher plant height at 30 and 60 days after the first cut, decreasing at 90 days, where the use of calcium in doses of 1.0 L / stood out he has; the numbers of tillers per plant at 30, 60 and 90 days after the first cut, obtained better averages with the use of Calcium at a dose of 1.0 L / ha; the number of leaves per bunch fluctuated between 4 and 6 leaves in the treatments studied; Applying Nitrogen in doses of 100 kg / ha at 30 and 60 days after the first cut and Nitrogen + Calcium in doses of 150 kg / ha of N + 2.0 L CaO, at 90 days after the first cut promoted the highest leaf width; the leaf length presented higher averages at 30, 60 and 90 days after the first cut using Calcium at a dose of 1.0 L / ha; the highest leaf area index, chlorophyll percentage, fresh weight and dry weight, at 30, 60 and 90 days after the first cut, reported higher averages using Nitrogen at a dose of 100 kg / ha and in the economic analysis it was reflected that The greatest net benefit was achieved by the treatment with nitrogen applied in doses of 100 kg / ha with a net benefit of $ 377.24.